Pengelolaan Kawasan Pariwisata (Studi di Balai Besar Taman Nasional Bromo Tengger Semeru) - Utami, Hadi Sri (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
The rating of tourists hygiene awareness is considered low inducing pollution in the form of waste which is commonly found in the tourist area of Mount Bromo. This reasearch aims to determine, identify and analyze the management of Mount Bromo tourist area conducted by Balai Besar of Bromo Tengger Semeru National Park (Balai Besar TNBTS) from the perspective of public administration functions known as w â€œPOSDCORBâ€ (Planning, Organizing, Staffing, Directing, Coordinating, Reporting, Budgeting which was proposed by Gullick. This study also has purpose to identify and analyze factors affecting the management of tourism area of Mount Bromo. This research uses qualitative method with descriptive analysis approach. The result shows that the management of tourism area of Mount Bromo conducted by Balai Besar TNBTS is not optimum due to some constraints in perspective of planning, staffing, and budgeting.